2008
DOI: 10.1364/oe.16.005934
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the distance between cut-wire-pair layers on resonance frequencies

Abstract: We studied both experimentally and theoretically the influence of the distance between adjacent cut-wire-pair layers on the magnetic and the electric resonances in the microwave-frequency regime. Besides the dependence on the separation between cut-wire pairs, along the electric-field direction, the electric resonance strongly depends on the distance between cut-wire-pair layers, while the magnetic resonance is almost unchanged. This contrast can be understood by the difference in the distribution of induced-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Commonly used artificial composites combine continuous metal wires 7 with magnetic resonances in split-ring resonators (SRRs) 8 or cut-wire pairs (CWPs). [9][10][11] A major drawback of those conventional structures is that the NRI bandwidth is too narrow to be useful for most practical applications. It was demonstrated that the broadband negative permittivity can be achieved by employing the low-frequency plasma of a continuous wire medium.…”
mentioning
confidence: 99%
“…Commonly used artificial composites combine continuous metal wires 7 with magnetic resonances in split-ring resonators (SRRs) 8 or cut-wire pairs (CWPs). [9][10][11] A major drawback of those conventional structures is that the NRI bandwidth is too narrow to be useful for most practical applications. It was demonstrated that the broadband negative permittivity can be achieved by employing the low-frequency plasma of a continuous wire medium.…”
mentioning
confidence: 99%
“…It was confirmed by theoretical study [16]. Besides the width dependence, the magnetic-resonance frequency also depends significantly on the length of the cut-wire pair [17], and the distance between the cut-wire pair layers [18]. A simple equivalent-circuit model proposed firstly by Zhou et al [17], and then improved by us previously [18].…”
Section: Resultsmentioning
confidence: 80%
“…Besides the width dependence, the magnetic-resonance frequency also depends significantly on the length of the cut-wire pair [17], and the distance between the cut-wire pair layers [18]. A simple equivalent-circuit model proposed firstly by Zhou et al [17], and then improved by us previously [18]. It was shown that the magnetic-resonance frequency is inversely proportional to the length and depends strongly on the width of the cut-wire pair.…”
Section: Resultsmentioning
confidence: 99%
“…It is consistent with the phenomenon observed in figure 6. The influence of distance between cut-wire pair layers, in other words, the a z lattice constant along the k direction on the resonance frequencies was studied both theoretically and experimentally detail in reference [23]. It was found that a z provides a subtle effects not only on the electric resonance but also on the magnetic one.…”
Section: Resultsmentioning
confidence: 99%